Gs-coupled GPCR signalling in AgRP neurons triggers sustained increase in food intake - Ken-ichiro Nakajima (Nature Portfolio, 2016)
Hypothalamic Agouti-related peptide (AgRP) neurons play a key role in regulating food intake. Here, the authors report a novel pathway in which activation of Gs-coupled receptors on AgRP neurons leads to robust, sustained increase in food intake.